Comparison of the Effectiveness of Emotion Regulation-Based Play Therapy and a Child-Centered Mindfulness-Based Intervention on Executive Functions in Children with Attention-Deficit/Hyperactivity Disorder - Chorami, Fatemeh; Mahmoodi, Armin (KMAN Counseling & Psychology Nexus, 2026)
This study aimed to compare the effectiveness of emotion regulation-based play therapy and a child-centered mindfulness-based intervention on executive functions in children with attention-deficit/hyperactivity disorder. The present study was a quasi-experimental pretest–posttest design with a control group and a one-month follow-up. The statistical population included children aged 6 to 12 years with attention-deficit/hyperactivity disorder who were referred to child counseling centers in Yasuj, Iran, during 2025–2026. Using purposive sampling and based on the inclusion and exclusion criteria, 45 children were selected and assigned to three groups: emotion regulation-based play therapy, child-centered mindfulness-based intervention, and control group, with 15 participants in each group. The first experimental group received 12 sessions of emotion regulation-based play therapy, and the second experimental group received 10 sessions of child-centered mindfulness-based intervention. The control group was placed on a waiting list and received no intervention during the study. Data were collected using the Conners Parent Rating Scale for screening and the Barkley Executive Functioning Scale for measuring executive functions. Data were analyzed using repeated-measures analysis of variance and Bonferroni post hoc test in SPSS version 27. The results showed that the main effect of time was significant for executive functions, F = 821.81, p < .001, partial η² = .95. The main effect of group was also significant, F = 8.41, p = .001, partial η² = .28. Moreover, the interaction effect of time and group was significant, F = 216.42, p < .001, partial η² = .91. Bonferroni comparisons indicated that both intervention groups showed significantly lower executive-function difficulty scores than the control group at posttest and follow-up, p < .001. However, no significant difference was found between the two intervention groups at posttest or follow-up. Emotion regulation-based play therapy and child-centered mindfulness-based intervention were both effective in improving executive functions in children with attention-deficit/hyperactivity disorder, and their effects remained stable at the one-month follow-up. Since no significant difference was observed between the two interventions, both approaches may be considered useful child-centered methods for reducing executive-function difficulties in this population.